A qualitative study to explore the drivers, perceived benefits, and barriers of mobile marketing adoption – the case of Mauritius - Sagan Mariusz; Sannegadu Rajesh; Pudaruth Sameerchand; Juwaheer Thanika Devi; Lamport John Matthew (International Journal of Management and Economics)
This qualitative study explored the factors affecting mobile marketing acceptance and adoption. Unlike existing studies that investigated the mobile marketing adoption factors from the end users’ perspective, this study has explored the challenges, opportunities, and implications of the state of art of mobile marketing from a multi-stakeholders’ perspective. To achieve the study’s objective, primary data were collected through a focus group meeting among several stakeholders. Findings revealed that many businesses acknowledge its strategic importance for their growth and sustainability although mobile marketing in Mauritius is still at an infant stage and has a promising growth. These exploratory results have important implications for policymakers, managers, and digital marketers of diverse sectors to promote the adoption of mobile marketing in Mauritius. The unique novelty of our study reinforces the new theoretical lens on the concept of mobile marketing despite diverse research studies in this field in both developed and developing states.